2008
DOI: 10.1021/ma702225k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oligo(vinyl phosphonate)s by High-Resolution Electrospray Ionization Mass Spectrometry:  Implications for the Mechanism of Polymerization

Abstract: Dimethyl vinyl phosphonate, diethyl vinyl phosphonate, and diisopropyl vinyl phosphonate were polymerized at 60 °C via free radical polymerization to give oligomers. High-resolution electrospray ionizationmass spectrometry was used to analyze the resulting oligo(vinyl phosphonate)s in order to elucidate their polymerization mechanism. The resulting mass spectra showed no evidence of polymer chains capped with initiator derived fragments as end groups. Instead, the mass spectra indicated that transfer reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…As with step‐growth and ionic polymerisations, the application of contemporary MS techniques to free radical polymerisations has been shown to carry enormous potential towards the deepening of our knowledge relating to reaction mechanisms. For instance over the various different conventional free radical polymerisations systems that have been studied using MALDI and/or ESI, all aspects of the general conventional free radical polymerisation scheme (initiation, propagation, termination and chain transfer processes) have been encompassed: MWDs obtained from mass spectra have been used to determine values for k p using PLP experiments,137–141 , j and more specifically to investigate the chain length dependence of these k p values;142–144 primary and/or secondary radical identification through chain end‐group determination has led to various insights into initiation processes;78, 145–151 end‐group characterisation has also been used to evaluate the dominant modes of termination in specified free radical polymerisation systems;145, 152–154 and mechanisms relating to chain transfer processes have been studied 155–162. Not only is the breadth of mechanistic information capable of being accessed via MS impressive, the power displayed by contemporary MS instrumentation in accessing this information can also be remarkable.…”
Section: Contemporary Mass Spectrometric Investigations Of Synthetic mentioning
confidence: 99%
“…As with step‐growth and ionic polymerisations, the application of contemporary MS techniques to free radical polymerisations has been shown to carry enormous potential towards the deepening of our knowledge relating to reaction mechanisms. For instance over the various different conventional free radical polymerisations systems that have been studied using MALDI and/or ESI, all aspects of the general conventional free radical polymerisation scheme (initiation, propagation, termination and chain transfer processes) have been encompassed: MWDs obtained from mass spectra have been used to determine values for k p using PLP experiments,137–141 , j and more specifically to investigate the chain length dependence of these k p values;142–144 primary and/or secondary radical identification through chain end‐group determination has led to various insights into initiation processes;78, 145–151 end‐group characterisation has also been used to evaluate the dominant modes of termination in specified free radical polymerisation systems;145, 152–154 and mechanisms relating to chain transfer processes have been studied 155–162. Not only is the breadth of mechanistic information capable of being accessed via MS impressive, the power displayed by contemporary MS instrumentation in accessing this information can also be remarkable.…”
Section: Contemporary Mass Spectrometric Investigations Of Synthetic mentioning
confidence: 99%
“…Indeed, MS from bulk polymerization of AMS without TCTA has confirmed that the dominant species is B-(M)-Z, where B-Z ¼ M [87]. In the same way, chain transfer to monomer has also been proven by MS to occur in RP of DMI [32] and several vinyl phosphonates [89]. Of course, it is most likely that transfer is from monomer to the radical, as this is the way transfer occurs with TCTA and solvent, and there is tautomeric stabilization of the product monomeric radical (see Figure 10.22).…”
Section: Transfer To Small Moleculesmentioning
confidence: 82%
“…In addition, b-scission and transfer reactions are frequently reported to take place in the absence [26] or in the presence of a chain transfer agent [27], to the solvent, to the monomer [28] or to the polymer [29]. MALDI-TOF-MS has been used not only to investigate propagation [30], but for evidencing irreversible termination in controlled free-radical polymerization [31].…”
Section: Introductionmentioning
confidence: 99%